Plasmodiophora brassicae-Triggered Cell Enlargement and Loss of Cellular Integrity in Root Systems Are Mediated by Pectin Demethylation - Stefanowicz, Karolina; Szymanska-Chargot, Monika; Truman, William; Walerowski, Piotr; Olszak, Marcin; Augustyniak, Adam; Kosmala, Arkadiusz; Zdunek, Artur; Malinowski, Robert (Frontiers in Plant Science, 2021)
Gall formation on the belowground parts of plants infected with Plasmodiophora brassicae is the result of extensive host cellular reprogramming. The development of these structures is a consequence of increased cell proliferation followed by massive enlargement of cells colonised with the pathogen. Drastic changes in cellular growth patterns create local deformities in the roots and hypocotyl giving rise to mechanical tensions within the tissue of these organs. Host cell wall extensibility and recomposition accompanies growth of the gall, influences pathogen spread and also pathogen life cycle progression. Demethylation of pectin within the extracellular matrix may play an important role in P. brassicae-driven hypertrophy of host underground organs. Through proteomic analysis of the cell wall we identified proteins accumulating in the galls developing on the underground parts of Arabidopsis thaliana plants infected with P. brassicae. One of the key proteins identified was the pectin methylesterase PME18; we further characterised its expression and conducted functional and anatomic studies in the knock-out mutant and used Raman spectroscopy to study the status of pectin in P. brassicae infected galls. We found that late stages of gall formation are accompanied with increased levels of Pectin Methylesterase 18 (PME18). We have also shown, that the massive enlargement of cells colonised with P. brassicae coincides with decreases in pectin methylation. In pme18-1 knock-out mutants P. brassicae could still induce demethylation; however, the galls in this line were smaller and cellular expansion was less pronounced. Alteration in pectin demethylation in the host resulted in changes in pathogen distribution and slowed down disease progression. To conclude, P. brassicae driven host organ hypertrophy observed during clubroot disease is accompanied by pectin demethylation in the extracellular matrix. The pathogen hijacks endogenous host mechanisms involved in cell wall loosening to create an optimal cellular environment for completion of its life cycle and eventual release of resting spores facilitated by degradation of demethylated pectin polymers.